Tanzania - The Rural and Micro Financial Services Project - Mohan, P. C. (World Bank, Washington, DC, 2012)
Findings Info briefs reports on good practice in ongoing operational, economic and sector work carried out by the World Bank and its member governments in the Africa Region. This issue reports on the Tanzania Rural and Micro Financial Services Project. The project was designed as a Learning and Innovation initiative (2000-2004) with support from an IDA credit of US$2 million. Its objectives were (i) the development of a common policy framework, based on internationally recognized best practices, for rural and microfinance initiatives in the country which would establish an enabling environment for rural and microfinance and increase the quality and returns of subsequent investments by the government agencies and other donors; (ii) increasing the level of knowledge and skills within the industry; and (iii) instituting a program of systematic tracking and analyzing of all related initiatives against a set of common criteria. This info brief gives information on the project impacts as well as lessons learned.